1994
DOI: 10.1093/oxfordjournals.jbchem.a124658
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Oligoguanylate to Scavenger Receptors Is Required for Oligonucleotides to Augment NK Cell Activity and Induce IFN

Abstract: Specific palindromic sequences in synthetic oligonucleotides are required to induce IFN and augment IFN-mediated natural killer activity. To study the mechanism of IFN induction by oligonucleotides containing palindromic sequences, we investigated the possible target molecules of the oligonucleotides. Oligo-1, a 30mer single-stranded oligonucleotide with oligoG sequences next to the active palindromic sequence (AACGTT), had more activity than oligonucleotides with oligoA, oligoC, or oligoT sequences. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 17 publications
2
68
0
Order By: Relevance
“…5 Indeed, previous studies have suggested that binding of oligos to the scavenger receptors is required for their immune stimulatory activities and that scavenger receptor competitors such as poly-Gs and fucoidan are inhibitory on the immune activation by EC and CpG ODN. [19][20][21] Several experiments were performed to explore the possibility of uptake inhibition in more detail. First of all, EC and CT DNA were mixed at a 1:1 ratio starting from 4 g/ml and the mixture was serially diluted.…”
Section: Resultsmentioning
confidence: 99%
“…5 Indeed, previous studies have suggested that binding of oligos to the scavenger receptors is required for their immune stimulatory activities and that scavenger receptor competitors such as poly-Gs and fucoidan are inhibitory on the immune activation by EC and CpG ODN. [19][20][21] Several experiments were performed to explore the possibility of uptake inhibition in more detail. First of all, EC and CT DNA were mixed at a 1:1 ratio starting from 4 g/ml and the mixture was serially diluted.…”
Section: Resultsmentioning
confidence: 99%
“…Oligo-dG sequences have complex effects on cells, including formation of macrophage-like colonies from bone marrow (30), inhibition of tumor cell growth (31), and costimulation of T cells (3) in addition to inhibition of macrophage responses to CpG DNA (14,22). Inclusion of dG runs in ODN may enhance their uptake by scavenger receptor (32), but it would be unwise to assume that all effects of oligo-dG are mediated by this receptor, as other proteins, such as a macrophage cytoplasmic protein, have shown preferential binding to G-rich ODN (30). Inhibition by runs of dG nucleotides probably also explains the inhibition of macrophage activation observed by Häcker et al (33), and their claim that inhibition was sequence independent may have been due to the confounding effects of PS-specific inhibition at higher concentrations (28).…”
Section: Discussionmentioning
confidence: 99%
“…In some circumstances, nucleic acid-binding receptors may play a role in stimulation by sODNs. Thus, runs of guanine (G), which can bind to the type I scavenger receptor by forming base-quartet-stabilized four-stranded helices, can promote the activity of stimulatory ODN for macrophages and lead to enhanced NK cell lytic activity and IFN-␥ production (25,26). Other cell surface molecules may also function as ODN receptors.…”
Section: Discussionmentioning
confidence: 99%